Pandangan Ulama Terhadap Prospek Alumni Ilmu Al Qur’an dan Tafsir di Kabupaten Labuhan Batu Utara - Muhammad Hafiz; Sukiman; Ali Darta (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to investigate the views of ulama regarding the prospects of Al Qur'an and Tafsir Science alumni in North Labuhan Batu Regency. Using a qualitative approach, this research explores the ulama's perceptions of the role and contribution of alumni in society, as well as the challenges they face in developing their careers. Data was collected through in-depth interviews with experienced scholars in the area.The research results show that ulama have high hopes for the role of alumni in strengthening religious and social values in society. They see alumni as spiritual leaders who can have a positive impact on education, da'wah and socio- religious activities. However, a number of challenges were also identified, including limited access to educational resources, changes in educational and scientific paradigms, and increasingly fierce competition in the job market. In facing these challenges, ulama recommend the need to continue to improve the quality of education and training for alumni, as well as strengthening collaboration between ulama and alumni in an effort to overcome challenges and take advantage of existing opportunities. In this way, alumni can develop their scientific potential optimally and make a significant contribution to the progress of society and the sustainability of religious values.